Kesejarahan Hadis dalam Tinjauan Teori Common Link - Rahmadi Wibowo Suwarno (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
This study entitled Kesejarahan Hadis Tinjauan Teori Common Link. The background of the study is study of authenticity, origin, and history of hadith has become an interesting topic and even a debate from the beginning of Islam until now. Interesting and a debate because it concerns the authenticity of Islamic teachings. Among the new theories and worldviews in contemporary criticism of contemporary hadith are the common link theory. For it is formulated the purpose of this study is to find out how to work and understand the implications of the theory of common links to the historic Hadith of the Prophet. The results of this study indicate that the common link theory impacts on the source or origin of hadith based on whom. Differences in interpreting common links determine which hadith comes from whom. Penelitian ini berjudul